The Effect of Social Environment on Employee Performance - Pratama, Yudhistira Anugerah; Yuliaty, Farida; Kosasih, Kosasih; Kadarisman, Sumeidi; Paramarta, Vip (International Journal of Digital Marketing Science, 2024)
The purpose of this study is to analyze how the social environment of Bukit Raya Sekawan Mining Company affects worker performance. This research employed a quantitative associative methodology. This research include all 45 workers of Bukit Raya Sekawan Mining Company as its population. Observation, interviews, literature reviews, documentation studies, observation guidelines, and questionnaires are some of the methods and instruments used for gathering data. The outcomes demonstrated the beneficial and substantial effect of the social environment. This means that in order to maximize the accomplishment of business objectives and guarantee employee welfare, Bukit Raya Sekawan Mining Company must keep an eye on and assess the social environment and employee performance. Regarding Bukit Raya Sekawan Mining Company, it is necessary to gather precise data for staff members in order to start social programs like team-building or mentorship, evaluate staff communications, and provide staff members chances for professional growth. In this manner, it is anticipated that in the future, Bukit Raya Sekawan Mining Company and its workers would work together to accomplish the goals, rights, and responsibilities as a single entity.